Preparation of magnetic polyurea microspheres by one-step precipitation polymerization. Issue 181 (13th June 2017) - Wang, Wen-Lin; Gao, Li-Long; Cong, Hai-Lin; Yu, Bing; Mou, Chun-Bo
ABSTRACT: Magnetic polyurea microspheres (MPUMs) were prepared by one-step precipitation polymerization of isophorone diisocyanate (IPDI) with water in the mixed solvent of water and acetone. Pre-prepared monodisperse and magnetic Fe3 O4 @SiO2 nanoparticles were added before polymerization. Then the surface morphologies of MPUMS were characterized by scanning electron microscopy (SEM). MPUMs exhibit good recycling stability assisted by the convenient magnetic separation. Therefore, MPUMs can serve as a promising carrier candidate for adsorption of dyes and treating sewage.